ANALISIS TREND FASHION WANITA IMPOR TERHADAP KEPATUHAN SYARIAH DAN PERILAKU KONSUMTIF MASYARAKAT - Rafiza Zuliani; Ulfazilah; Ridwan (Fakultas Ekonomi dan Bisnis Universitas Malikussaleh, 2026)
Abstract The trend of imported women's clothing sales in Langsa City tends to be inconsistent with sharia compliance and triggers consumer behavior, even though traders are required to follow market trends. This study aims to analyze the influence of this trend on sharia compliance and consumer behavior of the community using a qualitative approach through observation, interviews, and documentation. The results of the study indicate that: (1) Imported fashion trends cause a shift in Muslim women's clothing patterns due to variations in design, models, and quality, but some are not in accordance with sharia because they emphasize body curves and do not completely cover the aurat, although consumers still consider the quality of materials and durability. (2) This trend also encourages consumer behavior, such as impulsive purchases due to design and promotion, as well as excessive lifestyles for status and social image, so that purchasing decisions are not only based on function, but also symbolic value Keywords: Imported Women’s Fashion Trends, Sharia Compliance, Consumerist Behavior.